Mineral authigenesis within chemosynthetic microbial mats: Coated grain formation and phosphogenesis at a Cretaceous hydrocarbon seep, New Zealand. (28th August 2020) - Zwicker, Jennifer; Smrzka, Daniel; Steindl, Florian; Böttcher, Michael E.; Libowitzky, Eugen; Kiel, Steffen; Peckmann, Jörn
Abstract: Marine hydrocarbon seeps are sites of chemosynthetic microbial activity and authigenic carbonate formation. Seep limestones are typified by a range of geochemical signatures of microbial hydrocarbon oxidation, but only few seep deposits reveal mesofabrics that can be regarded as evidence of microbial activity. A Cretaceous methane‐seep limestone from Waipiro Bay, New Zealand, exhibits a fabric composed of cryptocrystalline carbonate fluorapatite between carbonate coated grains and spheroidal calcite. To understand the unusual Waipiro deposit, a paragenetic sequence has been derived for coated grains, spheroidal calcite and carbonate fluorapatite using thin section petrography, scanning electron microscopy, Fourier‐transform infrared spectroscopy and stable isotope geochemistry. The formation of 13 C‐depleted coated grains (δ 13 C values as low as −15.8‰ Vienna‐Pee Dee Belemnite) and spheroidal calcite (δ 13 C values as low as −21.3‰) was favoured by hydrocarbon oxidation. Fibrous banded and botryoidal cement, a typical early diagenetic phase of hydrocarbon‐seep deposits, features δ 13 C values as low as −22.9‰. Coated grains and spheroidal calcite grew by displacive growth in a gel‐like medium, probably a microbial mat. Phosphorus is a mobile element and marine pore waters are typically undersaturated with respect to carbonate fluorapatite. Specific conditions are consequently required to retain sufficient concentrations to precipitate carbonate fluorapatite. Possible sources of phosphorus for the formation of the 13 C‐depleted Waipiro carbonate fluorapatite (mean δ 13 C value of −15.4‰) include (a) the oxidation of sedimentary organic matter by organoclastic sulphate reduction, (b) the degradation of the microbial mat itself and (c) the active release of polyphosphate by sulphide‐oxidizing bacteria. This study suggests that the formation of the Cretaceous Waipiro seep limestone involved an interplay of biogeochemical processes including sulphate‐driven anaerobic oxidation of methane, organoclastic sulphate reduction and possibly nitrate‐dependent sulphide oxidation. It further demonstrates that coated grains resembling oncoids are not restricted to shallow water, photosynthesis‐dependent ecosystems. Abstract : Marine hydrocarbon seeps are sites of chemosynthetic microbial activity and authigenic carbonate formation. Seep limestones are typified by a range of geochemical signatures of microbial hydrocarbon oxidation, but only few seep deposits reveal mesofabrics that can be regarded as evidence of microbial activity. Coated grains, spheroidal calcite, and carbonate fluorapatite of the studied Waipiro deposit formed by an interplay of biogeochemical processes including sulphate‐driven anaerobic oxidation of methane, organoclastic sulphate reduction, and possibly nitrate‐dependent sulphide oxidation.